Causality and Science - Nalini Kanta Brahma (Prentice-Hall, 2007)
Causality and Science may at first sound as abstract and, perhaps, as esoteric subjects. For, while one seems to touch on the transcendental and the metaphysical realm, the other seems to be rooted on terra firma. However, while reading through this compact and concise book, written with great clarity and precision, one comes to realize that there is no clash between these two, and indeed reconciliation between them is possible.The author, with his remarkable erudition and scholarship, contends that the whole conception of science is so much bound up with the causal concept that it seems hardly possible that science could ever be able to do without it. He argues that space, time and causality are the three categories on which science is built.The book also shows that of the four causes - material, formal, efficient, and final, how the material and efficient causes are given prominence. In this process, the book demonstrates the inadequacy of the empirical view of causation, and shows that material cause combines with the efficient and final causes, or how these coalesce into one and only the adequate cause remains. There is no antagonism between the noumenon and the phenomenon or the Brahma and the Maya.Even though relativity may reign supreme for many, the author says that there is no opposition between perfect spontaneity and freedom and law and system on the one hand, and causality and determinism on the other. Ultimately, a reconciliation between causality and freedom can be effected, and the Reality that there is neither 'free' nor 'unfree', but transcends both the qualities can emerge as the Absolute which can solve for ever all oppositions. The book would be of interest to students of philosophy and any reader who has a philosophical and scientific bend of mind to delve deeper into the relation between causality and science.